The World Bank and Its Economic Missions - Moore, Frederick T. (The Review of Economics and Statistics, 1960)
B Y the spring of I958 the International Bank for Reconstruction and Development, as a part of its work in aiding underdeveloped countries, had sent major economic missions to fifteen countries: British Guiana, Ceylon, Colombia, Cuba, Guatemala, Iraq, Jamaica, Jordan, Malaya, Mexico, Nicaragua, Nigeria, Surinam, Syria, and Turkey.' published reports of these missions comprise the largest single collection of information extant on the problems and characteristics of underdeveloped economies. A careful reader of these reports is impressed with the wealth of detail and the obviously painstaking care with which the material has been assembled. Since more than seven years have now elapsed since the first report, it is appropriate to review this material and to ask how much has been learned about the process of development and also how successful the mission reports have been in diagnosing the key issues and in establishing development programs. What elements might we look for or expect to find in reports of this kind? First, since programs are dependent on good statistics, both to provide a basis on which to make decisions and to evaluate the effects of decisions once taken, some careful attention to the establishment of an effective social accounting system is to be expected. Second, the major outlines of a development program are required: the targets, the operational policies to achieve the objectives, the calculations of probable outcomes, etc. Flexibility is a virtue, but the outline should be internally consistent and unambiguous in showing the connection between the objectives and the means to those objectives. Third, in order for the programs to be implemented, a priority system for projects must be carefully delineated, and it must be shown that the priorities are consistent with fulfilling the development objectives. Fourth, in terms of the paths to development the real alternatives open to the country should be carefully surveyed, including estimation of the pay-offs and costs from alternative courses of action. Fifth, the price effects of development programs, probable inflationary pressures, and the effects on the balance of payments and the capacity to import require analysis. These are major elements which one might expect to find in a good economic development analysis; the list could be extended. In the remainder of this paper it is argued that the mission reports have covered these points inadequately, not at all, or ambiguously, with the result that the reports are unsatisfactory as economic analyses and unsuitable as guides to development programs. Before proceeding to the substantive argument, however, one qualification must be noted. These reports were prepared at different times, by different groups of people, for different countries. They do not all share the same faults or the same virtues. ensuing discussion should make it amply clear that the above criticisms do not apply in toto to all the reports, nor to any one report in particular. * This is a condensation of a report titled The Failures of the World Bank Missions, RAND Corporation, P-I4II, June 24, I958. I am indebted to my research assistant Mrs. Marjorie Hald for her help in surveying the reports. Dr. H. J. Barnett and Dr. Charles Wolf read the original manuscript and made many helpful comments. 'In chronological order the reports on these countries are: Basis of a Development Program for Colombia (I950); Economic Development of Guatemala (I95I); Economy of Turkey (I95I); Report on Cuba (I95I); Surinam: Recommendations for a Ten Year Development Program (I952); Economic Development of Jamaica (I952); Economic Development of Iraq (I952); Economic Development of Ceylon (I953); Economic Development of British Guiana (I953); Economic Development of Nicaragua (I953) ; Economic Development of Mexico (I953); Economic Development of Malaya (I955); Economic Development of Syria (I955); Economic Development of Nigeria (I955); Economic Development of Jordan (I957). Reports on British Honduras, Uruguay, and Somaliland have been issued in mimeograph form, but they are specialized and are not considered here. In June I957, a mission was sent to Thailand; although somewhat different in intent from previous missions, it will issue a report at some time. A summary of some of these reports appears in J. Spengler, IBRD Mission Economic Growth Theory, American Economic Review, XLIV (May I954), 583-99. Hereafter in this paper the reports will be cited by the country name.